Pemberdayaan Masyarakat Kabupaten Boyolali dalam Program Corporate Social Responsibility - Pratama, Panji Satria; Taufiq, Achmad; Astuti, Puji (Journal of Politic and Government Studies, 2017)
Sidomuncul Pte Ltd. is one of the companies that apply the corporate social responsibility activities that have empowerment herbal village program. The program aims to contribute to society and the environment, improve the community economy, strengthen destinations, tourist areas in Boyolali and the surrounding region, as well as improving rural welfare. Sidomuncul Pte Ltd in order to increase the capacity of communities also provide guidance and assistance cultivation of spices ranging from planting to managementIn this research by using descriptive qualitative research approach. Qualitative methods used authors wanted to examine qualitative methods used authors wanted to examine resulted image of corporate social responsibility program. At this research focuses on the activities of social responsibility undertaken Sido Muncul Pte Ltd. program of corporate social responsibility that has been created is intended to contribute to society and the environment, improve the community economy, strengthening tourist destinations And community empowerment program in Boyolali and its surroundings, and Improve the welfare of rural communitiesThe result of this research has already been planned program of empowerment from Sido Muncul Pte Ltd. Community interest in the high spice village program due to the availability of land to be managed and the majority of the livelihoods of the target villagers as farmers. The method used is the empowerment of socialization and training. Community participation in the empowerment indicated resources by the initiative participation Gapoktan (Farmers) in herbal village. Research has found that in 2016 the target villages still implement development activities. Herbal village program in Boyolali regency is the 2 implementation of the program: First implemented by the Regional Government of Boyolali through the Department of Agriculture, Plantation and Forestry and the second, implementation of corporate social responsibility of Sido Muncul Pte Ltd. that are Branding